Calder Pride - Dailey, Janet (New York Harper, 2000)
After her fiance is killed, Cat Calder, a Montana rancher's daughter vows never to marry, but sex with a stranger is acceptable. The result is a son and years later when the stranger is appointed sheriff and she faces danger her vow is tested.
80748
Keywords: Calder family (Fictitious characters) -- Fiction; Unmarried mothers -- Fiction; Ranch life -- Montana -- Fiction; Montana -- Fiction